Growing Up Under COVID-19: Young People’s Agency in Family Dynamics - Shah, Malika; Rizzo, Sara; Percy-Smith, Barry; Monchuk, Leanne; Lorusso, Enrica; Tay, Chermaine; Day, Laurie (Frontiers in Sociology, 2021)
The COVID-19 pandemic transformed the nature of family life in countries across the world. School, and workplace closures meant that families spent more time at home and had to confront new economic, social, and psychological challenges as a result of lockdowns and the greater proximity of family members. Policy, research and media coverage of the pandemic’s impact on family life has focused primarily on the economic costs borne by households. This article draws on the findings from an empirical research project funded by the UK Nuffield Foundation on “Politics, Participation and Pandemics: Growing up under COVID-19”, which worked with young people as co-researchers, to present an innovative perspective on the impact of lockdown on family relationships. The research team adopted a longitudinal ethnographic action research approach to document and make sense of the experiences of young people (aged 14–18) in four countries: Italy, Lebanon Singapore and the United Kingdom. The project used digital ethnography and participatory methods to track the responses of 70 young people to the challenges created by the pandemic. The study used the family as a prism for understanding how the lives of children and young people in different family circumstances and relationships were affected by the crisis. This article analyses, firstly, the complex shifting dynamics within households to identify the transformative effects of the pandemic on family life in various socio-cultural contexts. Secondly, it examines how young people’s agency shaped family dynamics. In conclusion, the authors recommend how the findings from the study can be used to inform government interventions designed to minimise the impacts of the pandemic on the social well-being and rights of children and young people, and to recognise them as active participants in family and civic life both during and after the pandemic